Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T18:15:43+01:00
A)-3x+5y=16/*2
-2x-4y=-62/*3
-6x+10y=32
-6x-12y=-186
-2y=-186+32
-2y=-154/(-2)
y=77
2010-02-25T19:01:20+01:00
A)
-3x+5y=16 |*2
-2x-4y=-62 |*(-3)

-6x+10y=16
6x+12y=186 +
_________________
22y=202 |:22
y=9,18 (w przybliżeniu)
-2x-4y=-62 |*(-1)
2x+4y=62
2x+4*9,18=62
2x=62-36,72
2x=25,28 |:2
x=12,64
y=9,18 ; x=12,64

b)
11x-12y=-13 |*(-5)
10x-20y=5 |*3

-55x+60y=65
30x-60y=15
_____________
-25x=40 |:(-25)
x=1,6
10x-20y=5
10*1.6-20y=5
-20y=5-16
-20y=-11 |:(-20)
y=0,55
x=1,6 ; y=0,55

c)
-x-y=-10
x-y=5 +
_________________
-2y=5 |:(-2)
y=-2,5
x-y=5
x-(-2,5)=5
x=5+2.5
x=7,5
x=7,5 ; y=(-2,5)

d)
5x-3y=15 |*2
-2x-4y=-15 |*5

10x-6y=30
-10x-20y=-75 +
______________
-26y=45 |:(-26)
y=-1,73 (w przybliżeniu)
-2x-4y=-15
-2x-4*(-1,73)=-15
-2x=-15+6,92
-2x=-8,08 |*(-1)
2x=8.08 |:2
x=4,04
x=4.04 ; y=1,73

* to mnożenie